Comparison of Adansonian Analysis and Deoxyribonucleic Acid Hybridization Results in the Taxonomy of Yersinia enterocolitica - Harvey, Sydney.; Pickett, M. J. (International Journal of Systematic and Evolutionary Microbiology, 1980)
A total of 190 strains of Yersinia enterocolitica from environmental sources, humans, and other animals were scored on biochemical, nutritional, and resistance tests. These were run in duplicate at 30 and 35°C, and the results were analyzed by numerical taxonomy. The computer-generated phenograms derived from simple matching coefficients and unweighted average linkage analysis delineated seven phenons from the 30°C data and five phenons from the 35°C data at a similarity value of 85%. A centrostrain was derived from each cluster in both matrixes, and these centrostrains were used as reference strains for subsequent deoxyribonucleic acid hybridizations. The relative binding ratios of the centrostrains to one another, as well as to other organisms of their own phenons, were determined. The genetic relationships as denoted by relative binding ratios were compared with the phenetic relationships developed by numerical taxonomy. Our results demonstrate that taxonomic relationships generated by numerical taxonomy do not necessarily correlate highly with those derived by deoxyribonucleic acid hybridizations in either a linear or a numerical sense (correlation coefficients, 0.48 and 0.40; mean correlation ratio, 0.60). In addition, it was found that numerical taxonomies may show considerable fluctuations in phenomic composition, which are dependent on the temperature of incubation. Deoxyribonucleic acid hybridizations among the various strains of this study divided the species Y. enterocolitica into at least four deoxyribonucleic acid relatedness groups. The level of intergroup homology was high enough (relative binding ratio, >20%) to justify the inclusion of all groups as species in the genus Yersinia.